Effects of Songs on Implicit Vocabulary Learning: Spoken-Form Recognition, Form-Meaning Connection, and Collocation Recognition of Iranian English as a Foreign Language Learners - Tilwani, Shouket Ahmad; Amini MosaAbadi, Fatemeh; Shafiee, Sajad; Azizi, Zeinab (Frontiers in Education, 2022)
This study explores the immediate and delayed impacts of songs on implicit vocabulary learning in terms of spoken-form recognition (SFR), form-meaning connection (FMC), and collocation recognition (CR) of Iranian intermediate female english as a foreign language (EFL) learners. For this purpose, a total of 150 female EFL learners, aged from 11 to 15, were selected from Iran Language Institute in Shahrekord City. The participants were randomly assigned into four experimental groups and two control groups. Two experimental groups and one control group took the pre-test, while for the other groups there was not any pre-test. Two experimental groups and one control group received immediate post-test whereas for the other groups there was not any immediate post-test. Nevertheless, all the groups took a delayed post-test. The data were obtained over five 90-min sessions. The control groups did not listen to any songs. Two experimental groups and one control group completed the immediate post-test. After 3 weeks, all the groups took the delayed post-test. The outcomes of a two-way ANOVA revealed that there was a statistically significant difference between the experimental group which received both pre-test and the treatment and the experimental group which received treatment but no pre-test. Additionally, the outcomes of a three-way ANOVA indicated that the experimental groups outperformed the control groups, giving rise to the conclusion that the treatment had been positively influential in improving the learners’ vocabulary learning. Finally, the outcomes of a one-way MANOVA showed that experimental groups and control groups performed differently with respect to SFR, FMC, and CR. Based on the findings, some implications are presented for different stakeholders.